Validation of a Measure of Flipped English Learning Readiness and Examination of Its Relationships With Instructional Practices, Learning Self-Efficacy, and Learning Beliefs - Luo, Shuqiong; Gan, Zhengdong (Frontiers in Psychology, 2022)
This study validated the Flipped English Learning Readiness Questionnaire, and examined its relationships with teacher instructional practices, English learning self-efficacy, and language learning beliefs. A total of 442 Chinese university EFL students voluntarily participated in this research. Exploratory and confirmatory factor analysis resulted in determination of five flipped English learning readiness factors (i.e., doing previews, in-class communication self-efficacy, positive experience, intentional behaviors, and self-directed learning) with a strong psychometric basis. The composite reliability, average variance extracted, and HTMT ratio of correlations further confirmed the convergent and discriminant validity of the Flipped English Learning Readiness Questionnaire. Structural equation modelling analysis suggested that English learning self-efficacy was a significant predictor of student flipped English learning readiness among students from different year-levels. Autonomy-supportive instructional practices significantly predicted Year 2 students’ self-directed learning while grammar/translation-oriented learning had a significantly positive influence on Year 3 students’ positive flipped learning experience and intentional behaviors.